The Need for a Paradigm Shift in Approaching Ageing-Related Design Research and Practice - Comincioli, Elena; Chirico, Alice; Gaggioli, Andrea; Masoodian, Masood (Frontiers in Psychology, 2021)
Despite a rapidly ageing world population, ageism – particularly in its implicit form – is widespread in society. In this article, we propose that a paradigm shift is needed in how we approach ageing-related research and practice. We also put forward the idea of using the Healthy Ageing framework of the World Health Organization as the basis for new lines of actions that can be taken by researchers and practitioners to address implicit ageism in society.